Historical studies on the use of Rhubarb in Japan - Ota, Misato; Makino, Toshiaki (Frontiers in Pharmacology, 2026)
BackgroundRhubarb product is the crude drug derived from the root or rhizome of Rheum or other related plants, and has been used since ancient times in Asian and European countries. However, the original plant species for Rhubarb product had been confused throughout its long history and across different areas.MethodsThe present study aimed to identify the original plant species for Rhubab products used in Japan through histological analysis of medicinal literature, successive Japanese Pharmacopoeias, and the textbooks of crude drugs published from the mid-Edo period (1603–1868) to the early Showa era (1926–1989).ResultsDuring the Edo period, Rumex madaio (synonym, Rumex daiwoo), a plant that grows wild in Japan, was initially recognized as the origin of Rhubarb product. However, our present study indicates that, after Rheum rhabarbarum was imported from continental China in the 16th century, it was cultivated as the origin of true Rhubarb product. Since Rhubarb product derived from Rheum rhabarbarum has weak laxative effects, it is reasonable to infer that strong laxative effects were not anticipated in Japan at that time. Meanwhile, Rhubarb product derived from Rheum palmatum was known in Japan as Russian Rhubarb. Rheum palmatum had spread from continental China to Europe via Russia, and had been introduced to Japan as a laxative when Dutch medicine was introduced in the late-Edo period. Since the Meiji era (1868–1912) in Japan, the use of Rhubarb product during the Edo period had been re-evaluated, and Rhubarb product in Japan had been registered in the Japanese Pharmacopoeia. However, the publications in the Meiji era were reluctant to recognize that the Rhubarb product known as Toh-Rhubarb used by Japanese traditional Kampo physicians had derived from Rheum rhabarbarum. As a result, the two Rhubarb products were distributed separately, apart from those derived from Rheum palmatum. One was used by Kampo physicians and derived from Rheum plants grown in continental China, and referred to as Toh-Rhubarb. The other, derived from Rheum rhabarbarum, was referred to as Wa-Rhubarb.ConclusionConsequently, the names and origins of Rhubarb products had been changed after the Meiji era from those used during the Edo period.